Penerapan Model Belajar Problem Based Learning (PBL) untuk Meningkatkan Hasil Belajar pada Siswa Sekolah Dasar - Hadi Suyitno (STIT Muhammadiyah Bangil Pasuruan, 2024)
This study aims to improve students' understanding of Theme 1 Subtheme 2 material through the application of the Problem Based Learning (PBL) learning model in grade VI B students of SDN 1 Baosan Lor, Ngrayun District. This study uses the Classroom Action Research (CAR) method with the Kurt Lewin model consisting of four stages: planning, action, observation, and reflection, which are implemented in two cycles. Data collection techniques include interviews, observation, documentation, and student learning outcome tests. Initial results showed that before the implementation of the PBL model, only 40% of students understood the material, while the rest still experienced difficulties. After the implementation of the first cycle with improvements in learning media and a more contextual approach, the learning completion rate increased to 64.71%. In the second cycle, improvements were made in time management, creating a pleasant classroom atmosphere, and providing follow-up learning, which succeeded in increasing the completion rate to 94.12%. The PBL model has been proven to be able to increase student active involvement, clarify conceptual understanding, and create more interesting and meaningful learning. Discussions with colleagues also help teachers develop more effective learning strategies, emphasizing the connection between theory and real-life practice. Based on these results, it can be concluded that the implementation of the Problem-Based Learning model is effective in increasing student understanding, motivation, and active participation in the learning process in elementary schools.